SEIZURE PATTERNS AND THERAPEUTIC PROGNOSIS IN ACTIVE EPILEPTIC PATIENTS FROM DIFFERENT ETHNIC GROUPS (The Research of Medical Science Review, 2024)
This paper aims to discuss epilepsy, which is a chronic neurological disease defined as recurring seizures leading to changes in the patients’ thinking, awareness, behaviour, social interactions as well as social and economic functioning. The cross-sectional study was conducted in Pakistan and sought to comprehend seizure characteristics, sociodemographic variables and treatment response within different ethnicities, 132 patients experiencing epilepsy from both urban and rural settings. Conclusions show that the generalized ones exist more frequently than the partial ones, with the involvement of male patients and those who are younger. Valproate is recognized as the most used AED for both the generalized and the partial epilepsy. It is established that polytherapy has better efficacy in the treatment for partial seizures while monotherapy and polytherapy have similar effects in treating generalized seizures. Head injuries and parental consanguinity are such important factors, which predict genetic factors. Also, the study focuses on the psychosocial problems related to the epileptic patients including stigma and discrimination resulting to the poor quality of life. The study emphasizes the significance of timely intervention, proper use of AED as well as correct perception dissemination; the overall target of which is better epilepsy care and enhanced patient outcomes in Pakistan.